Universal semantic communication - Juba, Brendan (Springer, 2011)
Is meaningful communication possible between two intelligent parties who share no common language or background? In this work, a theoretical framework is proposed in which it is possible to address when and to what extent such semantic communication is possible: such problems can be rigorously addressed by explicitly focusing on the goals of the communication. Under this framework, it is possible to show that for many goals, communication without any common language or background is possible using universal protocols. This work should be accessible to anyone with an undergraduate-level knowledge of the theory of computation. The theoretical framework presented here is of interest to anyone wishing to design systems with flexible interfaces, either among computers or between computers and their users.